The Anxiety Of The Millennial Generation And Its Solutions From The Perspective Of The Qur'an - Ahmad Faidlun Nawal; Ahmad Yusam Thobroni (Eduvest - Journal of Universal Studies, 2024)
In daily life, millennials have undoubtedly experienced distress, which can be interpreted as feelings of stress and anxiety. This research focuses on understanding distress from the perspective of the Qur'an, which serves as the primary guidance for Muslims. This study aims to explore the Qur'anic view on distress, the definition of distress in both language and the Qur'an, as well as understanding how millennials interpret distress, the terms used in the context of distress, and interpreting distress according to the Qur'an by providing solutions to improve the quality of life. This research adopts a qualitative descriptive approach that relies on literature study research, including Qur'anic verses, research publications, and related articles. In terms of interpretation, this research relies on the thematic interpretation method (tafsir maudhu’i). It also includes studies conducted by experts related to the phenomenon of distress, which encompasses stress and anxiety. In the context of the millennial generation, this research discovers solutions to overcome distress, which are further elaborated by the author through new ideas, especially by referring to relevant Qur'anic verses. The findings revealed in this research are 1) the Qur'anic view on stress as a test from Allah SWT, 2) that calamities are a source of stress, 3) the importance of having strong self-confidence, and 4) solutions for distress from the perspective of the Qur'an.